Comparison Between Bisection, Newton and Secant Methods for determining the root of the Non-Linear equation using MATLAB. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Bisection, Newton, and Secant Methods are indicated for demonstrating the numerical approximation of thenon-linear equation problem f(x) = ex + 2−x + 2 cos(x) − 6 = 0 . the paper wants to display the comparison ofimplementation, the convergence rate among methods of detect the root of the non-linear equation. The MATLAB R2015b isused to determine the root-finding problem within the desired closed interval [1, 2] and illustrate the numerical solutioncompared. The Newton and Secant are speedy to converge with very small error part and requiring a few steps of iterationswhile the bisection method is converged with taking too much computingof iterations. Consequently, the numericalapproximation solution of the methods on the sample problem interprets that the Newton and Secant are more absolutelyaccurate and efficient than the results achieved from the Bisection method.